UPAYA PENINGKATAN HASIL BELAJAR SENI MUSIK MELALUI METODE PEMBELAJARAN TUTOR SEBAYA PADA SISWA KELAS X MIA 1 SMA NEGERI I KOTO BESAR DHARMASRAYA - Elismarwati Elismarwati (STKIP PGRI Situbondo, 2021)
This research aims to improve the learning outcomes of the art of music through peer tutoring methods for students of Class X MIA 1 SMA Negeri I Koto Besar Dharmasraya. The research method used is classroom action research. Classroom action research was carried out in two cycles, the first cycle consisted of two meetings and the second cycle consisted of two meetings. Each meeting was carried out using the peer tutor learning method. As a data collection tool is to carry out a written test by students after the learning process is complete. This research was carried out with the steps of action planning, action implementation, evaluation and reflection for each cycle. By using peer tutor learning methods, it turns out that the level of student learning outcomes in learning Musical Arts shows an increase from the initial condition which has an average of 65.00. Meanwhile, in the first cycle, the average was 74.62 and in the second cycle, the average increased to 84.62. This shows that the learning outcomes of students' Musical Arts have improved from the first cycle to the second cycle, this indicates that the peer tutor learning method on the results of Music Arts Learning in Class X MIA 1 SMA Negeri I Koto Besar Dharmasraya.